2022
DOI: 10.1177/0192513x211056939
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on Constraints in Marital Satisfaction Among Married People in African Context

Abstract: Marriage is considered as the most important social institution and symbol of adulthood in Africa. However, the trend of divorce has increased alarmingly in recent years. We explored the constraints towards marital satisfaction by using the Delphi technique with assumptions that couples are the experts on their marriages. Participant’s panel included married heterosexual couples divided into two groups: men and women couple’s panels. The group of women’s panel included 31 participants and men’s panel contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Couple awareness to identify the type of conflict faced is essential to avoid conflicts that drag on and negatively impact children as well as their legal status (Elkhalloufi et al, 2021;Lucas, 2008;Piedalue et al, 2021;Shahin, 2020). Mediation principles such as good faith, confidentiality, and collaborative settlement are essential to achieving a win-win solution supported by appropriate mediators, advocates, and mediation venues (Chang et al, 2023;Guetto et al, 2022;Mwansisya & Mwampagatwa, 2023). Legal regulations such as Supreme Court Regulation No.…”
Section: Mediation Process In Religious Courtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Couple awareness to identify the type of conflict faced is essential to avoid conflicts that drag on and negatively impact children as well as their legal status (Elkhalloufi et al, 2021;Lucas, 2008;Piedalue et al, 2021;Shahin, 2020). Mediation principles such as good faith, confidentiality, and collaborative settlement are essential to achieving a win-win solution supported by appropriate mediators, advocates, and mediation venues (Chang et al, 2023;Guetto et al, 2022;Mwansisya & Mwampagatwa, 2023). Legal regulations such as Supreme Court Regulation No.…”
Section: Mediation Process In Religious Courtsmentioning
confidence: 99%
“…Previous research has shown that mediation as a method of resolving conflicts in the household is mandatory and should be done immediately (Bouland, 2022;Muhammad et al, 2021;Redding, 2021), with a third party who can achieve a win-win solution and protect the couple's secrets (Chang et al, 2023;Guetto et al, 2022;Mwansisya & Mwampagatwa, 2023). Couples who misidentify conflict can prolong problems, psychologically disturb children, and obscure legal status (Elkhalloufi et al, 2021;Lucas, 2008;Piedalue et al, 2021;Shahin, 2020).…”
Section: Introductionmentioning
confidence: 99%